2023
DOI: 10.3390/nu15092169
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Processed Food Intakes Are Associated with Depression in the General Population: The Korea National Health and Nutrition Examination Survey

Abstract: Depression is the most common mental illnesses worldwide. The consumption of ultra-processed food (UPF) has increased globally due to its affordability and convenience; however, only a few studies have investigated the link between UPF intake and depression in the general population. We investigated the associations between UPF and depression using the Korea National Health and Nutrition Examination Survey. A total of 9463 individuals (4200 males and 5263 females) aged above 19 years old participated in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…As this association became stronger when adjusted for other confounding factors, including adherence to the Mediterranean diet as a proxy for diet quality, the authors suggest that dietary components other than nutritional quality may play a role in the reported association. Similar results were observed in the Korean population of The Korea National Health and Nutrition Examination Survey, where 9463 subjects were analyzed [ 16 ]. However, in a sex-specific stratification, only women showed a significant association between higher UPF consumption and depression.…”
supporting
confidence: 83%
“…As this association became stronger when adjusted for other confounding factors, including adherence to the Mediterranean diet as a proxy for diet quality, the authors suggest that dietary components other than nutritional quality may play a role in the reported association. Similar results were observed in the Korean population of The Korea National Health and Nutrition Examination Survey, where 9463 subjects were analyzed [ 16 ]. However, in a sex-specific stratification, only women showed a significant association between higher UPF consumption and depression.…”
supporting
confidence: 83%
“…Part of this discourse has included emerging evidence pointing toward the addictive potential of ultra-processed foods [19][20][21]. Less attention has been paid to the growing relevance the nutrition sciences have to the behavioral sciences-research linking ultra-processed foods to mental disorders and various neuropsychiatric outcomes, including depression, anxiety [22][23][24][25][26][27][28][29][30], and antisocial and/or aggressive behavior [31][32][33][34][35][36][37] (Figure 1). The extent to which industry is responsible for promoting noncommunicable diseases, including mental disorders and addiction to ultra-processed food-like products, is described by criminal justice researchers under the banner of 'food crime' [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…The scientific literature has explored the association between ultra-processed foods and mental health in adults 12 , 13 , 14 , 15 , 16 , 17 and adolescents 18 , 19 . Studies have suggested that the consumption of ultra-processed foods may be associated with mental disorders 13 , 14 , 15 , 16 , 17 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The scientific literature has explored the association between ultra-processed foods and mental health in adults 12 , 13 , 14 , 15 , 16 , 17 and adolescents 18 , 19 . Studies have suggested that the consumption of ultra-processed foods may be associated with mental disorders 13 , 14 , 15 , 16 , 17 , 18 , 19 . However, regardless of the design, these studies only considered the intake of ultra-processed foods, without considering other food environment factors.…”
Section: Introductionmentioning
confidence: 99%